Safety, Immunogenicity and Efficacy of Prime-Boost Vaccination with ChAd63 and MVA Encoding ME-TRAP against Plasmodium falciparum Infection in Adults in Senegal - Mensah, Victorine A. (PLoS One, 2016)
Malaria transmission is in decline in some parts of Africa, partly due to the scaling up of control measures. If the goal of elimination is to be achieved, additional control measures including an effective and durable vaccine will be required. Studies utilising the prime-boost approach to deliver viral vectors encoding the pre-erythrocytic antigen ME-TRAP (multiple epitope thrombospondin-related adhesion protein) have shown promising safety, immunogenicity and efficacy in sporozoite challenge studies. More recently, a study in Kenyan adults, similar to that reported here, showed substantial efficacy against P. falciparum infection. One hundred and twenty healthy male volunteers, living in a malaria endemic area of Senegal were randomised to receive either the Chimpanzee adenovirus (ChAd63) ME-TRAP as prime vaccination, followed eight weeks later by modified vaccinia Ankara (MVA) also encoding ME-TRAP as booster, or two doses of anti-rabies vaccine as a comparator. Prior to follow-up, antimalarials were administered to clear parasitaemia and then participants were monitored by PCR for malaria infection for eight weeks. The primary endpoint was time-to-infection with P. falciparum malaria, determined by two consecutive positive PCR results. Secondary endpoints included adverse event reporting, measures of cellular and humoral immunogenicity and a meta-analysis of combined vaccine efficacy with the parallel study in Kenyan adults.We show that this pre-erythrocytic malaria vaccine is safe and induces significant immunogenicity, with a peak T-cell response at seven days after boosting of 932 Spot Forming Cells (SFC)/10(6) Peripheral Blood Mononuclear Cells(PBMC) compared to 57 SFC/ 10(6) PBMCs in the control group. However, a vaccine efficacy was not observed: 12 of 57 ME-TRAP vaccinees became PCR positive during the intensive monitoring period as compared to 13 of the 58 controls (P = 0.80). This trial confirms that vaccine efficacy against malaria infection in adults may be rapidly assessed using this efficient and cost-effective clinical trial design. Further efficacy evaluation of this vectored candidate vaccine approach in other malaria transmission settings and age-de-escalation into the main target age groups for a malaria vaccine is in progress.